Physical properties of honeys produced in the Northeast of Brazil - Patricia Argemira Costa; Izabel Cristina Freitas Moraes; Ana Mônica Q.B. Bittante; Paulo José do Amaral Sobral; Catarina A. Gomide; Celso C. Carrer (International Journal of Food Studies)
The aim of this work was to study the rheological, thermal and some other physical-chemical properties of selected honeys produced in the Northeast of Brazil. Two samples were produced by native “Jandaira” bees (Melipona subnitida) and ten other samples by Africanized bees (Apis mellifera). The samples were analyzed for pH, water activity (aW), soluble solids and water content. Viscosity flow curves were obtained using a rheometer (25ºC, 0-100s-1). Thermal analyses were performed on a differential scanning calorimeter, with heating rate of 10ºC/min (-100 to 100ºC). The water content and the pH of the honey samples varied from 17.2 to 27.9% and from 3.2 to 4.2, respectively, and, the aW of the samples varied from 0.57 to 0.74. Two samples were out of specification with respect to water content, according to Brazilian laws. In relation to rheology, all honey samples showed Newtonian behaviour with no thixotropy or dilatancy. The viscosity varied as an exponential function of the water content. The highest viscosity was obtained for the sample with lower values of water content and aW. Thermograms showed a glass transition (Tg) occurring between -52.4 and -42.6ºC, in the samples produced by Apis mellifera and -67.6 and -57.0ºC for the other samples. A linear relationship was obtained between Tg and water content. In conclusion, the honey viscosity depended on the water content of the product. The higher the water value and therefore the greater the aw, the lower viscosity and Tg of the samples.